Divergent Techniques of Attendance Management (International Journal of Scientific Research in Science and Technology, 2024)
In order to keep record of students or employees, tracking their presence and absence is important. This is done by attendance management system. Maintaining attendance record manually is not at all a feasible task and this also leads to human errors, consumes more time, increases administrative burden, it is also insecure, etc. To overcome with these issues various Attendance Management Systems are developed based on recent technological advancements. This paper gives a brief overview of diverse methods for tracking attendance.